Identification of possible salivary metabolic biomarkers and altered metabolic pathways in south american patients diagnosed with oral squamous cell carcinoma - de Sá Alves, Mariana [UNESP]; de Sá Rodrigues, Nayara [UNESP]; Bandeira, Celso Muller [UNESP]; Chagas, José Francisco Sales; Pascoal, Maria Beatriz Nogueira; Nepomuceno, Gabrielle Luana Jimenez Teodoro; da Silva Martinho, Herculano; Alves, Mônica Ghislaine Oliveira; Mendes, Maria Anita; Dias, Meriellen; Alves, Levy Anderson César; Almeida, Janete Dias [UNESP] (MDPI, 2021)
Oral squamous cell carcinoma (OSCC) represents 90% of oral malignant neoplasms. The search for specific biomarkers for OSCC is a very active field of research contributing to establishing early diagnostic methods and unraveling underlying pathogenic mechanisms. In this work we investigated the salivary metabolites and the metabolic pathways of OSCC aiming find possible biomarkers. Salivary metabolites samples from 27 OSCC patients and 41 control individuals were compared through a gas chromatography coupled to a mass spectrometer (GC-MS) technique. Our results allowed identification of pathways of the malate-aspartate shuttle, the beta-alanine metabolism, and the Warburg effect. The possible salivary biomarkers were identified using the area under receiver-operating curve (AUC) criterion. Twenty-four metabolites were identified with AUC > 0.8. Using the threshold of AUC = 0.9 we find malic acid, maltose, protocatechuic acid, lactose, 2-ketoadipic, and catechol metabolites expressed. We notice that this is the first report of salivary metabolome in South American oral cancer patients, to the best of our knowledge. Our findings regarding these metabolic changes are important in discovering salivary biomarkers of OSCC patients. However, additional work needs to be performed considering larger populations to validate our results.
Keywords: Biomarkers; GC-MS; Mass spectrometry; Metabolites; Metabolomics; Oral cancer; Oral squamous cell carcinoma; Saliva